2015
DOI: 10.1002/jmri.24956
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance multicenter comparison of different MR scanners for quantitative diffusion-weighted imaging

Abstract: A specific and widely accepted protocol for quality controls in DWI is still lacking. The DWI quality assurance protocol proposed in this study can be applied in order to assess the reliability of DWI-derived indices before tackling single- as well as multicenter studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 28 publications
3
72
3
Order By: Relevance
“…Hence studies assessing reproducibility of head and neck tissue [126,147,148] were also included in this review. Some studies used vendorindependent post-processing software packages to compute the ADC maps [56,125,126,137,140,148] while others used site-specific software packages either vendorspecific or locally developed [68,138,141,147] . Although some investigators demonstrated high variability in the measured ADC (27.1% for left liver lobe) with vendorindependent software packages [56] , others found less variability in the measured ADC using vendor-specific software [148] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence studies assessing reproducibility of head and neck tissue [126,147,148] were also included in this review. Some studies used vendorindependent post-processing software packages to compute the ADC maps [56,125,126,137,140,148] while others used site-specific software packages either vendorspecific or locally developed [68,138,141,147] . Although some investigators demonstrated high variability in the measured ADC (27.1% for left liver lobe) with vendorindependent software packages [56] , others found less variability in the measured ADC using vendor-specific software [148] .…”
Section: Discussionmentioning
confidence: 99%
“…Belli et al [140] . No parallel imaging technique was employed and vendor-independent software was used to generate the ADC maps.…”
Section: Reproducibility Of Adc Values In Vitromentioning
confidence: 98%
“…DW-MRI have been chosen because they can be used to compute maps of apparent diffusion coefficient (ADC), which have been shown to be very useful for tumor detection and characterization [11, 29, 30], evaluation of treatment response [5, 31], and tumor staging [8, 32]. Also, unlike other types of MRI, ADC maps have been shown to be useful to assess tumor cellularity, even across different scanners [33], provided that the same range of b values and the same field strength are used [34, 35]. …”
Section: Introductionmentioning
confidence: 99%
“…In this study, we acquired imaging data using the thickness of 5 mm in the axial images and 3 mm in the sagittal images. Third, previous study by Belli et al 25 demonstrated that a good agreement on ADC measurement was obtained over all the MRI centers. However, we did not explore whether the cut-off point of ADC value for epithelial tissue and carcinoma was reproducible for other 3.0 Tor 1.5 T MRI units.…”
Section: Discussionmentioning
confidence: 74%